Implementation Of Individual Guidance Through Whatsapp Group To Increase Achievement And Learning Motivation Of Students Of Class VII SMP Negeri 3 Ngaglik Sleman 2020/2021 - Suratmi Suratmi (Universitas Islam Indonesia, 2021)
This study aims to increase the learning motivation of seventh-grade students of SMP Negeri 3 Ngaglik Sleman through